A first case of ileocecal resection using a Senhance Surgical System in Japan - Hiroka Kondo; Shigeki Yamaguchi; Yasumitsu Hirano; Toshimasa Ishii; Nao Obara; Liming Wang; Masahiro Asari; Takuya Kato; Tetsuyoshi Takayama; Hirofumi Sugita; Shinichi Sakuramoto; Isamu Koyama (Surgical Case Reports, 2020)
Abstract Background Several manufacturers are in the process of developing various innovative systems and expect more options in the robot market. One of the latest systems, the Senhance® platform (TransEnterix Surgical Inc, Morrisville, NC, USA), has already been introduced in Europe and has also been approved for clinical use in Japan. We report the first case of colorectal resection using Senhance in Japan. Case presentation The patient was a 79-year-old Japanese man who visited a previous physician for positive fecal occult blood. Upon close inspection, the preoperative diagnosis was cT2N0M0 stage I. We performed surgery using Senhance. The operation time was 198 min, and the estimated amount of bleeding was 10 g. He was discharged after surgery without any major complications. However, it is also true that the operability of the conventional port arrangement was poor during the surgical operation. Conclusion We report the first Senhance-assisted ileocecal resection for colorectal cancer in Japan. In the future, we would like to find more ways to use it by accumulating more cases.